Sappi’s stakeholder engagement approach involves listening to multiple voices for social impact - Andre Oberholzer; Mpho Lethoko; Mari Lee; Dalien Benecke; Thabisile Phumo (Communicare)
Putting theory into practice remains a challenge in the diverse South African context. The authors of this case study seek to present a communication programme that have been implemented by African communication professionals and which illustrate the practical application of business and social impact results to communication theory. Sappi is an Africa-headquartered multinational company with a global footprint which uses its stakeholder approach as part of its business strategy. Sappi is a leading global provider of everyday materials made from wood-fibrebased renewable resources. The company works with its partners to build a thriving world by acting boldly to support the planet, people and prosperity (Sappi, 2023). This article critically evaluates how Sappi uses stakeholder engagement to achieve this purpose statement.